2016
DOI: 10.1021/acscatal.6b00886
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Reduction of Nitroarenes Using a Transition-Metal-Loaded Silicon Semiconductor under Visible Light Irradiation

Abstract: We investigated transition-metal-loaded silicon nanoparticles for the photocatalytic reduction of nitroarene derivatives in the presence of formic acid under visible light irradiation. Formic acid assumes the role of both a hydrogen source and a sacrificial reagent for the introduction of electrons into the generated holes of semiconductors. As such, in the presence of formic acid, photocatalytic reactions smoothly proceed under mild conditions without gaseous hydrogen. In particular, palladium-loaded silicon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 43 publications
0
62
0
Order By: Relevance
“…[13] Among them, FA is almosta ni deal candidate for CTH because of its nontoxicity, convenience, and recyclability. [14,15] Unfortunately,m any of the reportede fficient catalysts for CTH generally necessitate the use of noble metals, [9,[16][17][18][19][20] seriously limiting the large-scale applications owing to the highe conomic cost and low availability.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Among them, FA is almosta ni deal candidate for CTH because of its nontoxicity, convenience, and recyclability. [14,15] Unfortunately,m any of the reportede fficient catalysts for CTH generally necessitate the use of noble metals, [9,[16][17][18][19][20] seriously limiting the large-scale applications owing to the highe conomic cost and low availability.…”
Section: Introductionmentioning
confidence: 99%
“…However, in most of the photocatalytic hydrogenation routes, hydrogen donors such as formic acid, isopropyl alcohol or triethanolamine were used instead of gaseous H2. [11][12][13] Recently, we reported a photocatalytic reduction of nitroarenes with H2 using graphene-supported CoS2 particles as the catalyst under mild condition, however with unsatisfactory activity. 14 For catalytic hydrogenation of nitroarenes, dissociation of H2 is the rate-determining step.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Besides TiO 2 , Pd/Si, Ag/Bi 2 MoO 6 , PbBiO 2 X, and CdS have also been used for hydrogenation of the nitro group. 2024 A Pt-deposited Ti(IV) metal-organic framework has been reported for nitro reduction reactions with an initial reaction rate of 132 μmol h –1 g –1 . 25 Weiss et al have reported that electron transfer, not proton transfer, is the rate-limiting step for nitrobenzene reduction.…”
Section: Introductionmentioning
confidence: 99%